Pengaruh Agregat Pipih Pada Campuran Perkerasan Lentur Jalan Raya Hot Rolled Sheet-Wearing Course - Muhammad Aminsyah (Universitas Andalas, 2024)
Good highway construction depends on one factor, namely aggregate quality. Cubic, flaky and elongated aggregates are usually obtained from crushing large stones with a stone crusher. Cubic aggregates are the best form for their use because they have many sides to bind each other. This study aims to see the effect of using flat aggregates on flexible pavements of highways. This study uses a mixture of Hot Rolled Sheet Wearing Course (HRS-WC). This study compares standard mixtures that meet specifications (coarse aggregates using 10% flat aggregates) with several combinations of flat aggregate use in coarse aggregates. From the results of this study, the percentage of safe use of flat aggregates is 13.33%, which if the use of flat aggregates exceeds this value, the marshall parameters obtained are no longer in accordance with the specifications of the HRS-WC mixture.